2019
DOI: 10.5539/jfr.v8n3p1
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest Physiology, Biochemistry and Quality Management of Chili Plum (Spondias purpurea var. Lutea): A Review

Abstract: The chili plum (Spondias purpurea L.) is an exotic fruit with a climacteric pattern of respiration belonging to the Anacardiaceous family and is consumed in both the fresh and processed states. The fruit has a yellow pulp, pleasant aroma, sweet sour taste with vitamin A content being higher than cashew, guava, some papaya and mango cultivars. However, a relatively short shelf-life of 5-6 days at ambient temperatures for harvested fruits and widespread incidence of fruit-fly infestation are two major limitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
1
1
Order By: Relevance
“…Different authors have reported that Spondias purpurea L. fruits, shows climacteric behavior; however, some others did not detect climacteric behavior in evaluations carried out on the same species (Mohammed et al, 2019). In the present experiment, climacteric was not observed in the ecotypes 'Castilla' and 'Roja' (Figure 1 C and D).…”
Section: Respirationcontrasting
confidence: 65%
“…Different authors have reported that Spondias purpurea L. fruits, shows climacteric behavior; however, some others did not detect climacteric behavior in evaluations carried out on the same species (Mohammed et al, 2019). In the present experiment, climacteric was not observed in the ecotypes 'Castilla' and 'Roja' (Figure 1 C and D).…”
Section: Respirationcontrasting
confidence: 65%
“…The fruit of S. purpurea L. -commonly known as Mexican plum, jocote, or jobo in Mexico and as Lapa, Job, Moyo, Sta Roseno, Jismoyo, and De Cocer in other countriesis widely consumed in many regions of Latin America and the Caribbean (MOHAMMED et al, 2019), and has been since pre-Hispanic times (RUENES et al, 2010). The drupe is varied in shape (ovoid, round, or oblong), size (20-50 mm in longitudinal diameter), and weight (4-43 g) -possessing both a thick, fibrous endocarp as well as a pleasant-ly flavored/aromatic flesh (sweet but with a slightly acidic aftertaste, similar to that of a plum).…”
Section: Introductionmentioning
confidence: 99%